2017
DOI: 10.1111/hae.13292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnosis of von Willebrand disease on patient outcomes: Analysis of medical insurance claims data

Abstract: The inherited bleeding disorder von Willebrand disease (VWD) is challenging to diagnose owing to disease heterogeneity, lack of a definitive laboratory test and variations in diagnostic criteria. We evaluated the impact of diagnosis and diagnostic delay on patient outcomes. The PharMetrics Plus Database was interrogated for medical claims for VWD (ICD-9 286.4) and bleeding events between 1 January 2006 and 30 June 2015. Longitudinal analysis was performed of patients newly diagnosed with VWD (≥9 months' contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Thus, the number of patients with a VWD diagnosis, identified in the Danish registries, was comparable with that identified in Swedish registries. In a study using data from more than 100 million commercially insured patients in the United States, 32,028 individuals were diagnosed with WVD between 2006 and 2015 (9 years), an incidence which may be comparable to our findings or slightly higher, depending on the exact person‐time contributed 8,16 …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, the number of patients with a VWD diagnosis, identified in the Danish registries, was comparable with that identified in Swedish registries. In a study using data from more than 100 million commercially insured patients in the United States, 32,028 individuals were diagnosed with WVD between 2006 and 2015 (9 years), an incidence which may be comparable to our findings or slightly higher, depending on the exact person‐time contributed 8,16 …”
Section: Discussionsupporting
confidence: 81%
“…5,14,15 ), an incidence which may be comparable to our findings or slightly higher, depending on the exact person-time contributed. 8,16 We did not include a run-in period in our study, meaning that the patients identified during the first years of the study period may not be true incident cases. 21 During the study period, there has been technological advances in the field of VWD diagnosis, but these are mainly related to the diagnosis of VWD subtypes and do not seem to explain why we observe a rise followed by a fall in incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have developed or evaluated BATs with or without pediatric specific questions to identify children who may require further testing, validate the sensitivity of a tool among children with VWD or estimate the prevalence of clinically significant bleeding symptoms of VWD in a pediatric population to facilitate treatment . However, a more complete characterization of the bleeding symptoms among children with diagnosed VWD could help to improve management of this disorder in this younger population …”
Section: Introductionmentioning
confidence: 99%
“…Our findings should be interpreted with due consideration to the methods used for data collection. Findings from an analysis by Sidonio et al 23 have raised questions concerning the reliability of using ICD-9 claims data alone to identify patients with VWD. Sidonio et al also utilized ICD-9 codes (at least two claims for VWD) to identify patients with VWD, and found that less than two-thirds of patients had a diagnostic laboratory test within the 2 years before or after diagnosis.…”
Section: Limitationsmentioning
confidence: 99%